BUDAYA JAWA DALAM NOVEL SUTI KARYA SAPARDI DJOKO DAMONO - Manshur Manshur (LPPM UNISDA, 2017)
The purpose of the study is to describe the role of Javanese culture (priyayi culture, devotion culture, and ancestral culture) in Suti's novel by Djoko Damono. This research is qualitative descriptive research. The data in this research are tangible words, phrases, phrases, and sentences that indicate the existence of Javanese culture. The results show the following: 1) Priyayi in Javanese culture has inspired many people to look more deeply about the social interrelation of society, 2) In the analysis of the devotion of Suti figure, this research is focused on the stern attitude of facing, treating and witnessing the change of society from pre-modern to modern society, 3) The sense of devotion to the ancestors is an ideology deeply rooted in society.